PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA INDUSTRI PERKEBUNAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Chandra, Sally Anggraini (Jurnal KIAFE, 2023)
This research aims to examine the influence of profitability ratios, company growth and company size on company value. This research uses a type of research with a quantitative approach where the research data is in the form of secondary data. The population in this research is 24 companies in the palm oil plantation sector that have been listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 period. Determination of the sample was carried out using a purposive sampling method, therefore sample data was obtained from 13 companies or 65 research samples. The research method used in this research is a multiple linear regression analysis test using SPSS version 26. The results of the research show that the profitability variable which is proxied using Return On Assets (ROA) and company size which is proxied by size has a positive and significant influence on value. company. Meanwhile, the company growth variable which is proxied using the Assets Growth Ratio has no effect on company value.